Demographical Factors, Not Lifestyle Factors, Associated with the Increase of Random Blood Glucose in Coastal Areas - Nilam Yusika Sari; Susy K. Sebayang; Septa Indra Puspikawati; Desak Made Sintha Kurnia Dewi; Ayik M. Mandagi; Erni Astutik (Universitas Airlangga, 2018)
Introduction: Blood glucose is an important component in the body produced by the consumption of carbohydrates, proteins, and fats. A blood glucose imbalance causes an increase in the blood glucose level in the body. The occurrence of economic changes due to tourism may lead to a change in diet that can lead to increased blood glucose levels. This study aims to analyse the factors related to random blood glucose in people living in coastal tourism areas in BanyuwangiMethods: The study used a cross-sectional survey. A total of 112 respondents were recruited using the random sampling method, using two-stage cluster sampling techniques taken from the Head of household data in multiple villages. The factors studied included demographic, socioeconomic, lifestyle, and family health history.Results: The results showed that men had 28% higher random blood glucose compared to woman. People living in Bangsring had 31% higher random blood glucose compared to those in Buluagung.Conclusion: Local health care services should put extra effort into include men and those living in Bangsring in programs to prevent Diabetes Mellitus in coastal areas.